Shared leadership, value and risks in large scale transport projects: Re-calibrating procurement policy for post COVID-19. (December 2021) - Love, Peter E.D.; Ika, Lavagnon; Matthews, Jane; Fang, Weili
Abstract: Before the 2019 Coronavirus Disease (COVID-19) outbreak, the Australian Commonwealth and State Governments invested significantly in the upgrade and construction of large-scale transport infrastructure projects (>AU500 million). However, two trends prevail in Australia. Concessionaires/contractors face a requirement for fixed-price contracts, high levels of risk, and low margins. Concomitantly, an increasing number of projects have experienced significant cost blowouts, with adverse impacts on both the public and private sectors. Calls for the public sector to engage with collaborative procurement approaches to deliver large-scale transport projects, however, have gone unheeded. In this paper, we critically review existing policies and practices used to procure large-scale transport projects and examine the challenges they pose in a post-COVID-19 world. We suggest that the public and private sectors need to work in unison to overcome the significant economic hurdles that COVID-19 presents to the nation's infrastructure demands. We then proffer that governments need to re-calibrate their procurement policies to future-proof their large-scale transport infrastructure projects. To facilitate the process of re-calibration, we develop a theoretical procurement framework for consideration based on the concepts of shared leadership, value creation, and risks. It is envisaged that our procurement framework will provide a platform for engendering economic value and accounting for all-important societal costs and benefits in a world post pandemic. Highlights: Issues and challenges impacting the procurement of large-scale transport projects are identified. Suggests that the public sector needs to re-calibrate existing procurement policies. Proposes that public and private sector collaborate to share leadership, share value and share risks. Develops a new procurement paradigm that combines the principles of alliancing with PPI to create economic value.